Pengembangan Instrumen Tes Tipe Higher Order Thinking Skills (HOTS) Pokok Bahasan Bangun Ruang Sisi Datar - Ananda, Aulia; Sulasteri, Sri; Angriani, Andi Dian; Kusumayanti, Andi; Halimah, Andi (Faculty of Tarbiyah and Teacher Training, 2023)
This study aims to determine the process and analyze the quality of the HOTS-type test instrument development on flat side space and measure students' higher-order thinking skills. This type of research is research and development with the Formative Research (Tessmeer) model. The test subjects in this study were class XI.3 students at SMP Negeri 30 Makassar, totaling 30 students. Based on the research results, it is known that 1) the development process using the Formative Research (Tessmeer) model through 4 stages, namely the preliminary stage, the self-evaluation stage, the prototyping stage, and the field test stage. 2) the quality of test development is declared valid with a CVR (Content Validity Index) value, the average total score is 1 with a very appropriate category or is in the interval 0.68-1.00, practically based on the results of the questionnaire analysis of student responses 89.07% with the response category